MAHABBAH DAN MA’RIFAH DALAM TASAWUF DZUNNUN AL-MISHRI - Mina Wati (UIN Sunan Kalijaga Yogyakarta, 2019)
This article discusses mahabbah (the love of beings to God) and ma’rifah (the blessing of God to beings) that focuses on the thought of Dzunnun al-Mishri (hereinafter referred to as Dzunnun). The insufficiency of research on mahabbah and ma’rifah is the main reason for the requirement for further research related to the character and the relationship between this two concepts. So far, when talking about mahabbah, the most popular name is Rabiah al-Adawiyah. It is necessary to discuss about mahabbah and ma’rifah in the frame of thought of Dzunnun being resurrected. In addition, in this day and age, it is necessary for humankind to explore the concepts offered by Dzunnun given the many global impediment that cause humanity to drought in spirituality. This article is based on library or library research that examines library data by using descriptive analysis, interpretation and data analysis methods. The source used is secondary data which is used as a support for writing this article. The approach of Sufism with the general method of the Sufis is a prominent feature in the writing of this article. Ma’rifah is the highest level in the application of Sufism that can be achieved with Mahabbah. Every human being can do and feel mahabbah because in essence mahabbah creates servant’s love for the Creator. Meanwhile, ma’rifah is knowing or knowing God so that his heart can see God and he feels close to God. The relationship between the two can be said with the sentence, “love grows because of knowledge and cognition of God.” From that sentence, it can be seen that there is a correlation between mahabbah and ma’rifah. Ma’rifah can be obtained if humans have traced and felt mahabbah. Mahabbah is a feeling of closeness to God through love (spirit). Meanwhile, ma’rifah is the level of knowledge to God through the eyes of the heart (al-Qalb).